Nanotechnology to mitigate microbiologically influenced corrosion (MIC) - Kalajahi, Sara Taghavi; Misra, Archismita; Koerdt, Andrea (Frontiers in Nanotechnology, 2024)
Microbiologically influenced corrosion (MIC) is a crucial issue for industry and infrastructure. Biofilms are known to form on different kinds of surfaces such as metal, concrete, and medical equipment. However, in some cases the effect of microorganisms on the material can be negative for the consistency and integrity of the material. Thus, to overcome the issues raised by MIC on a system, different physical, chemical, and biological strategies have been considered; all having their own advantages, limitations, and sometimes even unwanted disadvantages. Among all the methods, biocide treatments and antifouling coatings are more common for controlling MIC, though they face some challenges. They lack specificity for MIC microorganisms, leading to cross-resistance and requiring higher concentrations. Moreover, they pose environmental risks and harm non-target organisms. Hence, the demand for eco-friendly, long-term solutions is increasing as regulations tighten. Recently, attentions have been directed to the application of nanomaterials to mitigate or control MIC due to their significant antimicrobial efficiency and their potential for lower environmental risk compared to the conventional biocides or coatings. Use of nanomaterials to inhibit MIC is very new and there is a lack of literature review on this topic. To address this issue, we present a review of the nanomaterials examined as a biocide or in a form of a coating on a surface to mitigate MIC. This review will help consolidate the existing knowledge and research on the use of nanomaterials for MIC mitigation. It will further contribute to a better understanding of the potential applications and challenges associated with using nanomaterials for MIC prevention and control.